Results of the evaluation of the unlined reclamation canals efficiency - Viktoria F. Talalaeva; Oleg A. Baev (Мелиорация и гидротехника)
Purpose: to estimate the efficiency of the unlined main and irrigation canals of reclamation systems, and to determine the effect of this parameter on the reduction in operational reliability and hydraulic characteristics of the canals (flow rate-velocity, filtration coefficient and roughness). Materials and methods. The study is based on the data obtained by the authors in the field studies of hydraulic and filtration parameters of a number of reclamation canals in the Southern and North Caucasian Federal Districts. To determine the efficiency, the classical empirical dependence of A. N. Kostyakov was used, as well as calculation formulas for determining seepage losses from continuously operating canals in an earthen channel with steady free filtration, recommended by SP 100.13330.2016. Results. Regulatory documents set inflated efficiency values at the level of 0.90–0.93, which are difficult to achieve in practice, especially for unlined canals. The values of the specific share of the reasons for the decrease in operational reliability that have the greatest impact on the canal efficiency were obtained. Due to the fact that this parameter is not constant for irrigation, main and distribution canals, when establishing it (or assigning it to the designed canals), it is necessary to take into account the possible limits of its change in the first years of canal operation and during their filling, when the filtration process is unsteady. Conclusions. Average statistical values of the efficiency for unlined and lined canals were established. The influence of flow-velocity and geometric parameters on this parameter was revealed. The main measures aimed at increasing the efficiency of unlined drainage canals were formulated.